Development of non-enzymatic screen-printed carbon electrode sensor for glucose using cyclic voltammetry - Bt Ahamad Mashat, Zamharirah; Abdullah, Faizuan; Abdul Wahab, Asnida; Faiz Md Shakhih, Muhammad; Suzziani Roslan, Anis (Environmental and Toxicology Management, 2022)
Enzyme-based sensors frequently produce unsatisfactory results such as poor reproducibility and insufficient long-term stability due to the natural instability of enzymes, stringent experimental conditions, and complicated immobilization procedures. Thus, an electrochemical non enzymatic sensor was fabricated by deposition of the multi-walled carbon nanotube (MWCNT) with zinc oxide nanoparticles (ZnO NP) and also molecular imprinted polymer (MIP) on a screen-printed carbon electrode (SPCE). Then, the modified electrode (SPCE/MWCNT/ZnO/MIP) was formed on the surface area of the SPCE. This study wanted to demonstrate the glucose detection between molecular imprinted polymer (MIP) which contained glucose as template, o-phenylenediamine (oPD) and potassium persulfate as initiators in 0.1 M PBS at pH 7 and   non-imprinted   polymer (NIP) without   addition   of   the   template.   The characterization and evaluation of various factor such as sensitivity, selectivity and limit of detection (LOD) were investigated through cyclic voltammetry (CV) and scanning electron microscopy (SEM) was used to look up onto the surface area of the modified electrode. The SPCE/MWCNT/ZnO/MIP electrode sensor showed a linear glucose concentration range from 0, 0.5, 1, 2 to 5 mM (R2 = 0.9709). The sensitivity of the sensor was 0.3386 μA mM-1 cm-2 with low detection limit of 1.81 mM. The sensor showed good stability and reproducibility along with excellent anti-interference properties to ascorbic acid, lactic acid, tartaric acid, and acetic acid. Finally, the applicability of the as-prepared SPCE/MWCNT/ZnO/MIP electrode sensor was successfully studied for detection of glucose. The results obtained for our sensor confirm that it is a promising non-enzymatic glucose sensor to be used for practical purpose.